Antitumor effect of sorafenib and mammalian target of rapamycin inhibitor in liver transplantation recipients with hepatocellular carcinoma recurrence. Issue 7 (23rd July 2018) - Jung, Dong‐Hwan; Tak, Eunyoung; Hwang, Shin; Song, Gi‐Won; Ahn, Chul‐Soo; Kim, Ki‐Hun; Moon, Deok‐Bog; Ha, Tae‐Yong; Park, Gil‐Chun; Ryoo, Baek‐Yeol; Lee, Kyung Jin; Kim, Nayoung; et al.
Abstract : Both sorafenib and mammalian target of rapamycin inhibitor (mTORi) have antitumor effects. This study aimed to evaluate their antitumor effects in liver transplantation (LT) recipients with hepatocellular carcinoma (HCC) recurrence. We performed a laboratory study using sorafenib and mTORi and subsequently validated their survival benefit in a clinical LT setting. In the laboratory study, the HepG2.2.15 liver tumor cell line and 5 patient‐derived graft HCC cell lines were used for in vitro cytotoxic studies. After treatment with everolimus and sorafenib, cell viability and apoptosis assays revealed noticeable cytotoxic effects with individual agents and augmented effects by combination therapy. An in vivo mouse study also demonstrated similar cytotoxic outcomes. In the clinical study including 232 LT recipients with HCC recurrence, the 3‐month medication drop‐out rate was 35.6% for sorafenib administration and 23.5% for mTORi administration. Postrecurrence survival rates were not different according to sorafenib administration ( P  = 0.17) but were significantly improved following mTORi administration ( P  < 0.001). In mTORi subgroups with and without sorafenib, there was no difference in the overall postrecurrence patient survival period ( P  = 0.26), indicating an absence of synergistic or additional antitumor effect from sorafenib. The median progression‐free and overall survival period was 6.4 and 11.8 months, respectively, after sorafenib administration. Time of tumor recurrence and use of mTORi were independent risk factors. In conclusion, our laboratory study demonstrated synergistic antitumor effects of sorafenib and mTORi, but this was not reproduced in our clinical LT study. Our clinical result of mTORi administration showed improved postrecurrence survival, thus administering mTORi in LT recipients with HCC recurrence appears worthwhile. However, the antitumor effect of sorafenib on posttransplant recurrence was not determined in this retrospective study, thus requiring further studies with early start of sorafenib administration. Liver Transplantation 24 932–945 2018 . © 2018 AASLD.